PENERAPAN KURIKULUM 2013 PADA MATA PELAJARAN IPS DI SMP - Dessilva Rievqa Devega; Mashudi Mashudi; Aminuyati Aminuyati (Universitas Tanjungpura, 2019)
AbstractThis study aimed to know the implementation of the curriculum on Social Sciences to Year-7 Students of SMP Negeri 14 East Pontianak. The form of research which used descriptive with the qualitative. Resources of the data were from Headmaster, Curriculum Representative, Social Sciences (IPS) teacher to Year-7 of class B, D, E and the data were syllabus, lesson plan and results from an interview with the headmaster, curriculum representative and Social Sciences teacher. It showed the best structure which was appropriate to the 2013 curriculum format Lesson plan (RPP) and assessment as well as the result of interview with them. It showed had already of the syllabus was good because it was accordance with the 2013 curriculum, the implemented of learning process was also good because the teacher had followed by the steps to steps of learning existing in the lesson plan, and assessment had been already good could be seen teachers have done the assessment when the learning process takes place based on aspects of attitude, knowledge and skills, then the constraints faced by teachers because of the complexity 2013 curriculum. Keywords: Implementation of 2013 Curriculum, Social Studies